PENDAMPINGAN PENDAFTARAN LEGALITAS USAHA MIKRO KECIL MENENGAH DI DESA BENTO KABUPATEN KERINCI - Saridewi, Artika; Aldiansyah, Rizky; Nilda, Elvi (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Various problems are faced by micro, small, and medium enterprises (MSMEs) in rural areas I nobtaining business legality, including the absence of funds to take care of legality, the difficulty of correspondence, and a lack of knowledge and information. This community service is carried out to help MSME actors destroy the legality. This activity was carried out in three stages, namely: (1) a survey of the number of MSME actors in Bento village; 2) provide counseling on the importance of legality and mechanisms; and (3) provide assistance in business registration to obtain a trading business license (SIUP) through the Online Single Submission (OSS) system. This activity will be carried out for one month in 2022. The results of the activity show that there are 7 MSMEs that need to be registered immediately. However, of the 7 registered, only 4 MSMEs were successful. One of the challenges is that entrepreneurs have not complied with certain standards. The internet connection is also frequently interrupted.